2018
DOI: 10.4314/ijbcs.v11i5.47
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical evaluation and GC-MS analysis of <i>Hyptis verticillata</i> cultivated in Calabar Cross River State, Nigeria

Abstract: Hyptis verticillata is a medicinal plant reported to possess strong antioxidant activity growing in the American continent with no evidence of its cultivation in Nigeria. The present study was designed to investigate the phytocompounds present in n-hexane extract of the leaves of H. verticillata cultivated in Calabar, Cross River State, Nigeria. The phytochemicals found in relatively high amounts were flavonoids (19.67±1.53%), phenols (13.20±0.40 mg/g) and saponins (7.17±1.04%). Others including phytates (0.42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…On the other hand, some compounds were detected in only one species of seaweed in this study, which include Cetene (J. adhaerens), Desmosterol (D. suhrii) and Oleic acid (P. africanum). From these three compounds, Cetene (also known as 1-Hexadecene) was intensively reported in extract of plants such as Citrus limon 33 , Gleichenia pectinata 34 and Hyptis verticillata 35 . Kebelmann et al 36 reported that Cetene where detected only in three species of polar seaweeds (Monostroma arcticum, Sphacelaria plumose and Kallymenia antarctica), out of thirteen species evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some compounds were detected in only one species of seaweed in this study, which include Cetene (J. adhaerens), Desmosterol (D. suhrii) and Oleic acid (P. africanum). From these three compounds, Cetene (also known as 1-Hexadecene) was intensively reported in extract of plants such as Citrus limon 33 , Gleichenia pectinata 34 and Hyptis verticillata 35 . Kebelmann et al 36 reported that Cetene where detected only in three species of polar seaweeds (Monostroma arcticum, Sphacelaria plumose and Kallymenia antarctica), out of thirteen species evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…3,5-bis(1,1-dimethylethyl)-4hydroxybenzene propanoic acid (11.27%) methyl ester is a unique compound that was detected a retention time antioxidant, anti-inflammatory properties (Mujtaba et al, 2020). Hexadecane (10.91%) is a hydrocarbon that possesses, antioxidant, antifungal & antimicrobial activities (Egbung et al, 2017). Tribullus terrestris plant extract could be an effective solution to combat establishment of UTI infections.…”
Section: Discussionmentioning
confidence: 99%
“…A fatty acid, 9,12-octadecadienoic acid, has been previously reported to have anticancer and antimicrobial effects [ 36 , 37 ]. Although the anticancer effects of the other two identified fatty acids, cyclopropanetetradecanoic acid, 2-octyl-, methyl ester and methyl 14 methylpentadecanoate, have not been evaluated, their antimicrobial effects have been previously reported [ 29 , 30 ]. Desulphosinigrin is a glucosinolate that has also been reported to have anticancer and antimicrobial effects [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%